Women sport injuries: a retrospective study of elite windsurfers - Penichet-Tomás, A.; Alonso-Fernández, D.; Gutierrez-Sanchez, A.; Andreu-Cabrera, E.; Suárez-Llorca, C. (Journal of Human Sport & Exercise, 2012)
This study was designed to identify the injuries of professional women windsurfers, from their anatomical location, type of sport, context when they occurred, type of injury, the time of inactivity as a result of the same, the type of health care received and the relationship between the number of injuries and the position in the final classification of professional windsurfing competitions. We gave a retrospective questionnaire to 18 women elite windsurfers, who took part in the World Cup competition held in Fuerteventura (2008). Women are injured more frequently during training than competition (77.8%; p<0.05 vs. 20.5%). Women suffer leg injuries more than men (83.3%; p<0.05 vs. 14.3%) in freestyle. Serious injuries were more frequent for women (66.7%; p<0.05 vs. 28.2%) and the time of inactivity due to the injury was shorter for women (50%; p<0.05 vs. 20.5%). These results indicate that female windsurfers are more liable to suffer injuries, generally serious, during training sessions. Freestyle involves a greater risk of leg injuries for women. The knee is the area where most injuries occur, both for men and women, followed by the legs.